LOW-COST DIGITAL MARKETING STRATEGIES FOR SMALL CULINARY BUSINESSES IN THE SOCIAL MEDIA ERA - Muhammad Khadafi Khadafi (GREET, 2024)
This study explores how small culinary businesses adopt low-cost digital marketing strategies to remain competitive in the social media era. Employing a qualitative design with interviews of 20 entrepreneurs, focus groups with 30 consumers, and analysis of social media engagement metrics, the research found that visual storytelling—through photos, videos, and interactive content—emerges as the most powerful approach to attract and retain customers. Results also show that collaborations with micro- and nano-influencers provide higher authenticity and engagement at a fraction of the cost of celebrity endorsements, while proactive reputation management, especially through online reviews, significantly boosts consumer trust and sales performance. These findings underscore the critical role of social media analytics in enabling entrepreneurs to adapt campaigns in real time, which aligns with evidence that agile businesses can increase revenues by up to 30%. This study contributes to filling a research gap by focusing on resource-constrained culinary SMEs in emerging economies, highlighting how affordable digital marketing can substitute for traditional advertising in saturated markets. Nevertheless, limitations include the small and localized sample size, suggesting that future studies should adopt mixed-method approaches and examine additional tools such as email marketing and search engine optimization. Overall, the research confirms that low-cost digital marketing is essential for small culinary businesses to enhance visibility, foster customer loyalty, and sustain long-term growth.